2011
DOI: 10.1891/0886-6708.26.6.788
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Status and Experiences of Abuse Among College Students

Abstract: Studies that explore experiences of abuse among deaf or hard of hearing college students are sparse and usually focus on lifetime experiences rather than the college years. A random sample of more than 1,000 college students at a campus in Upstate New York provided the data for this study. An institute for the deaf or hard of hearing was one of the colleges at the university and provided a unique opportunity to explore experiences among this demographic. Victimization rates and experiences by auditory status--… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
33
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 30 publications
5
33
1
Order By: Relevance
“…If we use the results from the model with all cases and no interaction effect from Table 3(a) and Table 4(a), we see that students that were Deaf or hard of hearing were 3 times more likely to report both psychological and physical abuse than hearing students. These findings are consistent with previous studies that have found that Deaf and hard of hearing students are significantly more likely to report abuse than their hearing peers (Anderson & Leigh, 2010;Porter & McQuiller Williams, 2011a;Porter & McQuiller Williams, 2011b), and highlight the importance for education among groups about their varying risks for different types of abuse. Students who are Deaf or hard of hearing, for example, may be exposed to "disability-specific forms of violence" by partners, such as destruction of communication devices (Powers et al, 2009(Powers et al, : p. 1041 (Anderson et al, 2011: p. 204).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…If we use the results from the model with all cases and no interaction effect from Table 3(a) and Table 4(a), we see that students that were Deaf or hard of hearing were 3 times more likely to report both psychological and physical abuse than hearing students. These findings are consistent with previous studies that have found that Deaf and hard of hearing students are significantly more likely to report abuse than their hearing peers (Anderson & Leigh, 2010;Porter & McQuiller Williams, 2011a;Porter & McQuiller Williams, 2011b), and highlight the importance for education among groups about their varying risks for different types of abuse. Students who are Deaf or hard of hearing, for example, may be exposed to "disability-specific forms of violence" by partners, such as destruction of communication devices (Powers et al, 2009(Powers et al, : p. 1041 (Anderson et al, 2011: p. 204).…”
Section: Discussionsupporting
confidence: 92%
“…Even though Deaf and hard of hearing women were more likely to report psychological abuse, it was not nearly as strong an effect as that for Deaf and hard of hearing men. Consistent with previous research (Porter & McQuiller Williams, 2011b), this suggests that disability has a different impact on victimization rates for men and women. Disability theory seems to be supported for men, but not for women.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations